Ways of thinking on entropy and spontaneity for undergraduate in chemistry from the theory of conceptual profiles - Cleiça Rafaela de Almeida Guimarães; Flávia Cristiane Vieira da Silva; Jose Euzebio Simões Neto (ACTIO: Docência em Ciências, 2019)
The present work is part of a broader academic master’s research, whose objective is to analyze the emergence of zones of the conceptual profile of entropy and spontaneity in a didactic sequence applied to chemistry graduates. We justify the use of the theory of conceptual profiles for its importance in considering different ways of thinking scientific concepts, which have pragmatic value in certain contexts, as well as the need to present this plurality in situations of teaching and learning in the classroom. This study is a clipping with the specific objective of analyzing the emergence of the zones of the conceptual profile of entropy and spontaneity from the informal and scientific conceptions of the students. The research was carried out with twenty students enrolled in the Physics-chemistry I course of the Licentiate degree in Chemistry of the Campus Acadêmico do Agreste of the Universidade Federal de Pernambuco, using an instrument composed of a single broad question, elaborated according to the literature recommendations: "the What do you mean by entropy?" The analysis showed the emergence of the three zones of the conceptual profile of entropy and spontaneity in students' answers, namely: perceptive/intuitive zone, empirical zone and rationalist zone. We highlight the occurrence of responses mostly associated with the idea of entropy as a degree of disorder of a system, in direct association with the question of the spontaneity of the processes by increasing entropy, which corresponds to the empirical zone.